Effect of the TAAR1 Partial Agonist Ralmitaront on Presynaptic Dopamine Synthesis Capacity Measured Using [F]DOPA PET in Naïve and Cocaine-Treated Mice - David R. Bonsall PhD; Michelle Kokkinou PhD; Els F. Halff PhD; Grazia Rutigliano PhD; Sac-Pham Tang MSc; Mattia Veronese PhD; Elaine E. Irvine PhD; Dominic J. Withers FRCP, PhD; Lisa A. Wells PhD; Sridhar Natesan PhD; Irene Gerlach PhD; Štefan Holiga PhD; et al. (Molecular Imaging)
Purpose Elevated dopamine synthesis capacity is part of the pathophysiology of schizophrenia thought to underlie psychosis. Drugs that reduce this phenomenon could thus be potential treatments for these disorders. In this study, we evaluated the ability of the trace amine-associated receptor 1 (TAAR1) partial agonist ralmitaront to reduce presynaptic dopamine synthesis capacity. Procedures Ralmitaront (3 mg/kg, i.p.), a TAAR1 partial agonist, was evaluated using [ 18 F]DOPA PET for its ability to modulate presynaptic dopamine synthesis capacity in naïve mice as well as mice in an induced hyperdopaminergic state following acute cocaine administration (20 mg/kg, i.p.). Results Cocaine treatment on its own did not induce elevated dopamine synthesis capacity when compared to the control group. Pretreatment with ralmitaront significantly reduced dopamine synthesis capacity when given either alone (44%) or in combination with the psychostimulant cocaine (50%) when compared to the control group. Conclusions The TAAR1 agonist ralmitaront reduces striatal dopamine synthesis capacity, indexed as Ki Mod , both in naïve animals and when given prior to acute cocaine. This indicates the potential of TAAR1 agonism to address disorders characterized by striatal hyperdopaminergia.